2017
DOI: 10.1155/2017/1654907
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Triple Therapy Containing Ilaprazole, Levofloxacin, and Amoxicillin as First-Line Treatment in Helicobacter pylori Infections

Abstract: Background and Aims. To establish the efficacy and safety of ilaprazole, levofloxacin, and amoxicillin as a first-line eradication treatment for Helicobacter pylori. Methods. Patients with gastric ulcer, duodenal ulcer, or gastritis, as detected by esophagogastroduodenoscopy with confirmed H. pylori infection between September 2014 and November 2015, were enrolled in the study. All participants received ilaprazole (10 mg bid), levofloxacin (500 mg bid), and amoxicillin (1000 mg bid) for 10 days. H. pylori erad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A review of levofloxacin‐based third‐line therapy over the past decade in Korea found pooled eradication rates of 71.6% throughout the decade, suggesting no increase in resistance rates over the past decade . A 10‐day triple therapy containing ilaprazole, levofloxacin, and amoxicillin reported good results, with an eradication rate of 88.8% …”
Section: Fluoroquinolonesmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of levofloxacin‐based third‐line therapy over the past decade in Korea found pooled eradication rates of 71.6% throughout the decade, suggesting no increase in resistance rates over the past decade . A 10‐day triple therapy containing ilaprazole, levofloxacin, and amoxicillin reported good results, with an eradication rate of 88.8% …”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…41 A 10-day triple therapy containing ilaprazole, levofloxacin, and amoxicillin reported good results, with an eradication rate of 88.8%. 42…”
Section: Fluoroquinolone Smentioning
confidence: 99%
“…In addition, Suki et al demonstrated a positive association between H. pylori infection and increased BMI (especially in patient groups with obesity). Furthermore, high BMI and stroke were associated with unsuccessful eradication, using 13 C‐UBT at 6‐8 weeks after initiation of therapy …”
Section: Noninvasive Testsmentioning
confidence: 99%
“…Furthermore, high BMI and stroke were associated with unsuccessful eradication, using 13 C-UBT at 6-8 weeks after initiation of therapy. 22…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%
“…The e cacy of present pharmacological treatments for H. pylori infection has evaluated in different studies [8][9][10][11][12][13][14]. The co-administration of a proton-pump inhibitor (PPI) and two antibiotics (triple therapy), or addition of bismuth salts to the triple therapy (bismuth-based quadruple therapy) for a period of 14 A block randomization method was used in order to assign patients randomly into permuted treatment blocks and ensure equal numbers in each group of treatment.…”
Section: Introductionmentioning
confidence: 99%